L’URSS face à la guerre du Golfe, une stratégie singulière - Lecours, Francine (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1986)
Soon after the opening of hostilities between Iran and Iraq in September 1980, the Soviet Union offered military assistance to Tehran while simultaneously suspending arms deliveries to Baghdad, a formerly faithful client. Following Iran s refusal of assistance, and possibly in reaction to a percieved threat from the spreading of Iran's Islamic revolution, Moscow re-opened arms shipments to Iraq. This ambivalent behavior on the part of the Soviet Union is partially explained by the history of its interests in the region. The Soviet Union has long Had strategic ambitions to bring Iran under its influence. Moscow welcomed any opportunity to increase economic and political des with Tehran even if in the short term the results were only partial. On the other hand, Iraq is an influential member of the Arab community - a useful relationship for the USSR, and one that while mutually1987 advantageous for both parties, has not required extensive commitments. One cannot ignore the possibility that important events in the Gulf War will cause an abrupt shift in Soviet attitudes and actions in the region.